O uso de medidas antidumping no Brasil, na Índia e na China: Características de regulaç\~ao e de participaç\~ao do setor privado - Daniel Ricardo Castelan (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This paper analysis the application of AD measures by Brazil, India and China between 1995 and 2010 and exams the participation of these countries in the trade defense negotiations at the Doha Round of World Trade Organization (WTO). The paper proposes the hypothesis that different decision making procedures and different patterns of relationship between the government and private sector in these countries partially explain the results of the AD investigations initiated by Brazil, India and China.
Keywords: F13; 330; trade policy; antidumping; WTO; international trade